Periventricular rather than deep white matter hyperintensities mediate effects of hypertension on cognitive performance in the population-based 1000BRAINS study. Issue 12 (18th December 2022) - Gronewold, Janine; Jokisch, Martha; Schramm, Sara; Himpfen, Heiko; Ginster, Theresa; Tenhagen, Isabell; Doeppner, Thorsten R.; Jockwitz, Christiane; Miller, Tatiana; Lehmann, Nils; Moebus, Susanne; Jöckel, Karl-Heinz; et al.
Abstract : Objectives: White matter hyperintensities (WMH) of presumed vascular origin are frequent in cerebral MRI of older people. They represent a sign of small vessel disease, are promoted by arterial hypertension, and relate to cognitive deficits. The interdependence of blood pressure and its treatment, WMH, and cognitive performance has not systematically been studied in population-based studies. Methods: Consequently, we analysed the interdependence of SBP, DBP, and antihypertensive medications, as well as BP/treatment category, with WMH and cognitive performance in 560 participants of the population-based 1000BRAINS study. Results: BP, its treatment, and BP/treatment category were moderately associated with cognitive performance (e.g. unadjusted β  = −0.10, 95%CI = −0.19 to −0.02 for the association of SBP (per standard deviation of 17.2 mmHg) with global cognition (per standard deviation of 0.5 z score)]. The harmful effect of BP on cognition was strongly mediated by periventricular hyperintensities (PVH), which were significantly associated with both SBP [ β  = 0.24, 95% CI = 0.14–0.34 (per 1-point-increase in Fazekas score)] and global cognition ( β  = −0.22, 95%CI =  −0.32 to −0.13). Thus, PVH mediated as much as 52% of the effects of SBP on cognitive performance. Mediation was less strong for deep white matter hyperintensities (DWMH, 16%), which showed less association with SBP ( β  = 0.14, 95% CI = 0.05–0.24) and global cognition ( β  = −0.12, 95%CI = −0.21 to −0.03). Regarding different cognitive domains, PVH most strongly mediated effects of SBP on nonverbal memory (94%) and executive function (81%). Conclusion: Our results indicate that PVH may predispose to cognitive impairment associated with hypertension, especially in the domains of nonverbal memory and executive function. Abstract :